Comment on Johnson's creating dimensional stock-flow inconsistency in Binswanger's model. Issue 2 (3rd April 2019) - Gilányi, Zsolt
ABSTRACT: Binswanger (2009 ) constructed a model of a pure credit money economy with production to demonstrate the existence of growth imperative in such economies. This model entails a misspecification because money may disappear from the economy at the alleged minimal steady state growth rate (Gilányi 2015 ). Johnson (2015 ) attributes this inconsistency to the confusion between the stock of outstanding loans at the end of period and the flow of loans taken during the period; that he calls dimensional stock-flow inconsistency. On the grounds of this criticism he modifies some flows to eliminate the problem raised by Gilányi. Binswanger (2015 ) omits this criticism because it is a simple misinterpretation of his model; rather he explains the inadequacy of Johnson's specification of flows. Doing so, he makes believe that there is still an unsettled debate on whether to treat loans as stocks or as flows in his model. This note demonstrates that both model specifications are dimensionally stock-flow consistent. Hence, Johnson's criticism is just a narrative behind the rationale of altering flows in the model; the controversy is not on dimensional stock-flow inconsistency but on the logically coherent specification of the magnitude of flows in the model.